Increasing Students' Interest in Islamic Learning through the Sorting Card Method at SD Negeri 31 Koto Pulai - Sawal; Supriadi; Herlina, Sri (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to improve students' interest in learning Islamic religious education by using the Sorting card method. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were high school students. The data for this study were obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that the Sorting card method can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 44.71%, the first cycle 65.39% and in the second cycle it increased to 87.66%. Thus, the use of the Sorting card method can be used as an alternative to improve student learning outcomes in Islamic religious education learning.